Kinematic analysis of rugby lineout throws in the Six Nations Tournament. [Análisis cinemático de los saques de lateral en el Torneo de Rugby del Seis Naciones]. - Ignacio Martín; Pablo Mira; José María Salinas; Luis Vaz; David Carreras (Ramón Cantó Alcaraz, 2018)
Abstract This study examines 126 successful, six- or seven-man lineouts of the 2013 Six Nations Tournament. Data were extracted from footage of the competition to calculate kinematic variables along with jumper position. Through cluster analysis, six types of throw were identified according to distance and velocity: short-fast, short-slow, medium short-fast, medium short-slow, medium long and long. Significant differences were detected in all the variables examined depending on the throw category (throw distance P<0.001; Partial eta square η2=0.932, height P=0.032; η2=0.096, flight time P<0.001; η2=0.789, starting angle P<0.001; η2=0.502, initial velocity P<0.001; η2=0.767 and jumper position P<0.001; η2=0.641). In the discriminant analysis, all variables except jumper position were able to correctly classify 100% of the throws. In addition, we differentiated the six participating teams, finding significant differences in throw height (Scotland vs England difference means d=0.32m, Ireland d=0.36m or France d=0.37m), flight time (Italy vs England d=0.34s or Ireland d=0.33s) and angle (Italy vs England d=9.72º or Ireland d=8.49º and Scotland vs England d=8.27º or Ireland d=7.04º). Our findings have implications for training and team analysis (own and rival) and also provide direction for future investigations. Resumen El presente estudio ha investigado 126 saques de lateral ganados con seis o siete jugadores en el alineamiento del torneo de las Seis Naciones de 2013 La observación se ha realizado a partir del estudio de los videos, por lo que los datos están extraídos en competición real. Un análisis cluster nos ha permitido establecer seis tipos de lanzamientos en función de la distancia y la velocidad: cortos-rápidos, cortos-lentos, mediocortos-rápidos, mediocortos-lentos, mediolargos y largos. Hemos encontrado diferencias significativas en todas las variables estudiadas en función de los tipos de lanzamiento (distancia del lanzamiento P<0.001; η2=0.932, altura P=0.032; η2=0.096, tiempo de vuelo P<0.001; η2=0.789, ángulo de salida P<0.001; η2=0.502, velocidad inicial P<0.001; η2=0.767 y posición del saltador P<0.001; η2=0.641). El análisis discriminante incluyó todas las variables excepto la posición del saltador, clasificando correctamente el 100% de los casos. Además, hemos diferenciado a los seis equipos participantes encontrando diferencias significativas en altura (entre Escocia con Inglaterra d=0.32m, Irlanda d=0.36m y Francia d=0.37m), tiempo de vuelo (entre Italia con Inglaterra d=0.34s e Irlanda d=0.33s) y ángulo de salida (entre Italia con Inglaterra d=9.72º e Irlanda d=8.49º y de Escocia con Inglaterra d=8.27º e Irlanda d=7.04º). Del presente trabajo se derivan implicaciones para el entrenamiento, el análisis del equipo propio y del rival y para futuras investigaciones en los saques de lateral.